2014
DOI: 10.3109/10715762.2014.929120
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ phosphorylation is an upstream event of GSK3 inactivation-mediated ROS generation in TGF-β1-induced senescence

Abstract: Transforming growth factor β1 (TGF-β1) induces Mv1Lu cell senescence through inactivating glycogen synthase kinase 3 (GSK3), thereby inactivating complex IV and increasing intracellular ROS. In the present study, we identified protein kinase C delta (PKCδ) as an upstream regulator of GSK3 inactivation in this mechanism of TGF-β1-induced senescence. When Mv1Lu cells were exposed to TGF-β1, PKCδ phosphorylation simultaneously increased with GSK3 phosphorylation, and then AKT and ERK were phosphorylated. AKT phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Herein, we are the first group to establish that rottlerin reduce Nox/ROS signal induced by PMA in brain astrocytes. The finding is consistent with previous study indicated that PKCδ phosphorylation is an upstream event of GSK3 inactivation-mediated ROS generation in TGF-β1induced senescence [43]. It is consistent with previous report indicated that rottlerin induces cyclooxygenase-2 upregulation through reactive oxygen speciesindependent pathway in HEI-OC1 cells [44].…”
Section: Discussionsupporting
confidence: 93%
“…Herein, we are the first group to establish that rottlerin reduce Nox/ROS signal induced by PMA in brain astrocytes. The finding is consistent with previous study indicated that PKCδ phosphorylation is an upstream event of GSK3 inactivation-mediated ROS generation in TGF-β1induced senescence [43]. It is consistent with previous report indicated that rottlerin induces cyclooxygenase-2 upregulation through reactive oxygen speciesindependent pathway in HEI-OC1 cells [44].…”
Section: Discussionsupporting
confidence: 93%
“…More recently, we demonstrated that BBR reduced DAG levels in palmitate-treated insulin resistant H9c2 cells [9]. Overexpression of wild type or a constitutively active PKCδ mutant was shown to decrease mitochondrial oxygen consumption in Mv1Lu cells [18]. In the current study, BBR treatment of H9c2 cells attenuated the palmitate-mediated increase in membrane-associated PKCδ yet still resulted in a reduction in OCR.…”
Section: Discussionsupporting
confidence: 61%
“…Iron chelation using deferoxamine (DFO) decreased complex II activity via down-regulated translation of the complex II iron-sulfur subunit, prior to increasing p27 kip1 -mediated cell cycle arrest, and eventual induction of senescence in Chang normal liver cells (21, 22). Transforming growth factor β1 (TGF β1) triggered senescence of Mv1Lu lung epithelial cells by inhibiting complex IV activity via the PKCδ/GSK3 axis, and increasing ROS (2325). Ionizing radiation induced endothelial cell senescence through a mitochondrial respiratory complex II defect and superoxide generation (26).…”
Section: Mitochondrial Dysfunction and Its Link To Dna Damage Responsesmentioning
confidence: 99%